PERSOALAN BAHASA DALAM AGAMA - Sudiarja, A. (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2007)
In his linguistic theory Ferdinand de Saussure distinguished between language in proper sense (la langue) such as English, France, Indonesian etc. and language in awider sense (la langage). Both however are systems of signs that fall into semiotics. It is in the second sense, that we can assume religion as a certain kind of language or as having proper language of its own. In the spirit of religious dialog in recent years, in which many different religions try out to communicate each other, the significance of religious language becomes apparent. It is urgent therefore, to clarify the meaning as well as the role of this language in theprocess of dialog. This article assumes that in each religions we can notice two kinds of language, which function quite differently; one is 'to express' the collective passion of the people, 'referring to' the religious reality and their experiences of it, whereas the other is 'to explicate' the meaning of that same reality, 'inducing' to discourses, in order to find proper conceptswhich will widen their comprehension of the religious notions. Only trough improving this second kind of language, which happens both in theological discourse and the study of holy scriptures, religions can improve their ability to communicate each other.